Perancangan Sistem Pakar Untuk Diagnosa Tanaman Pinang Yang Diserang Penyakit Dengan Metode Forward Dan Backward Chaining di Kabupaten Pidie - Asbahani Adytia (Yayasan Sagita Akademia Maju, 2024)
The design of an expert system for diagnosing areca nut plants attacked by disease with forward and backward chaining methods in Pidie Regency is a search process starting from the aim of obtaining conclusions that are solutions to the root of the problem. Data needs in the form of symptoms, pests are associated with so as to produce a result report. This application is developed with PHP programming language and MySQL database. This system works in order to present plant diagnostic information.